Spaghetti worms from the reef: two new species of Loimia (Polychaeta: Terebellidae) from Bora-Bora and Moorea (Society Islands, French Polynesia) and a range extension of L. tuberculata Nogueira, Hutchings & Carrerette, 2015 - Hutchings, Pat; Daffe, Guillemine; Glasby, Christopher; Lavesque, Nicolas (Zootaxa, 2025)
Two new species of coral-reef inhabiting Loimia are described: L. poraporaensis sp. nov., from the lagoon at Bora-Bora, French Polynesia and Hawaii and L. aimehoensis sp. nov., from Moorea in French Polynesia. Loimia poraporaensis sp. nov. has large lateral lobes on segments 2 and 3, a smooth body and eye spots absent. Loimia aimehoensis sp. nov. has banded buccal tentacles, large lateral lobes on segments 2 and 3, with those on segment 3 extending dorsally and with a basal flange, a smooth body and eye spots absent. These species are morphologically and molecularly compared to other recently described species from Pacific coral reefs. This study also allowed us to expand the known distribution of Loimia tuberculata from the type locality at Lizard Island (northern Great Barrier Reef, Australia) Southern GBR, Western Australia, eastern Papua New Guinea and New Caledonia. We provide two maximum likelihood trees (COI and 16S genes) for all species of Loimia for which data are available, as well as an identification key and a table of the diagnostic characters for the species of Loimia of this Pacific region. We also discuss their habitat and association with living corals.